Multiple Promoters Contribute to Swarming and the Coordination of Transcription with Flagellar Assembly in Salmonella - Wozniak, Christopher E. (American Society for Microbiology (ASM), 2010)
In Salmonella, there are three classes of promoters in the flagellar transcriptional hierarchy. This organization allows genes needed earlier in the construction of flagella to be transcribed before genes needed later. Four operons (fliAZY, flgMN, fliDST, and flgKL) are expressed from both class 2 and class 3 promoters. To investigate the purpose for expressing genes from multiple flagellar promoters, mutants were constructed for each operon that were defective in either class 2 transcription or class 3 transcription. The mutants were checked for defects in swimming through liquids, swarming over surfaces, and transcriptional regulation. The expression of the hook-associated proteins (FlgK, FlgL, and FliD) from class 3 promoters was found to be important for swarming motility. Both flgMN promoters were involved in coordinating class 3 transcription with the stage of assembly of the hook-basal body. Finally, the fliAZY class 3 promoter lowered class 3 transcription in stationary phase. These results indicate that the multiple flagellar promoters respond to specific environmental conditions and help coordinate transcription with flagellar assembly.